ELECTROCHEMICAL FREQUENCY MODULATION ANALYSIS OF (3AR,6AR)-3A,6A-DI-P-TOLYLTETRAHYDROIMIDAZO[4,5-D]IMIDAZOLE-2,5(1H,3H)-DITHIONE AS A CORROSION INHIBITOR FOR CARBON STEEL IN 1M HCl MEDIUM - Khasan Berdimuradov; Kuvonchbek Haydarov (American Journals Publishing, 2024)
Anticorrosion properties, EFM intermodulation spectra, EFM charts, time-versus corrosion rate, corrosion current, corrosion resistance, anodic and cathodic Tafel constants of (3ar,6ar)-3a,6a-di-p-tolyltetrahydroimidazo[4,5-d]imidazole-2,5(1H,3H)-dithione inhibitor for carbon steel in a 1M HCl environment were investigated by using new electrochemical frequency modulation analysis method. The obtained results suggest that the inhibitor molecules influence the electrochemical cathodic and anodic half-reactions, forming an insoluble protective layer on the steel surface, and maximally neutralizing the carbon steel surface, and reduce the hydrogen- and chloride-free ions attacks. EFM results’ accurate degrees were determined by causality factors.
Keywords: EFM, intermodulation spectrum, Tafel constants, anticorrosion inhibitor, causality factor.